KERAGAAN KOMODITAS LADA INDONESIA (Studi Kasus di Kabupaten Bangka) - ELIZABETH, ROOSGANDHA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 1 Februari 2005, 2012)
It has been admitted that plantation sub-sector as an important one compared with the others in agricultural sector. Pepper is one of the plantation commodities that traditionally contributes to the Indonesia’s foreign exchange. This commodity is also the oldest and native species of Indonesian spices, which has been marketed in the world wide. But, in the current situation, which is the still adversely affected by global economic crises, the pepper export has been decreased, even how days, the pepper production is lower then Vietnams. This decreased production of pepper, especially for example in Bangka district, is caused by inefficiently traditional management, with high cost, lack of labors, and uncertainly of pepper price, which is still controlled by middle-man. In order to improve the sub-sector plantation, especially the pepper plantation, it is needed to revitalize the extension program and further provide the credit scheme for farmers.
Keywords: Pepper, Plantation, Commodities, Export PENDAHULUAN